The Effect of Progressive Muscle Relaxation on Reducing Anxiety in Cancer Patients: Literature Review - Primasari Mahardhika Rahmawati; Mashuri; Chandra Dwi Ardianto (KHD Production, 2024)
One of the symptoms of cancer is the emergence of pain and anxiety related to each other, especially in patients who suffer from cancer. This can be caused by pain from cancer, examinations carried out and treatment that sufferers undergo. Anxiety can be caused by uncertainty about the prognosis of the disease, the effectiveness of treatment for recovery of the condition, which is often found in cancer patients, especially at an advanced stage. Anxiety management is provided through the main nursing interventions, namely progressive muscle relaxation techniques. The purpose of this study was to identify progressive muscle relaxation to reduce anxiety in cancer patients. The method used is a literature review in the form of a literature review obtained from Garuda Ristekbrin, PubMed, Google Scholar and Science Direct searches. After filtering, the author examines the contents of the article in accordance with the subject matter in accordance with the author's title. There were 10 journals selected for review by the authors, 6 of which used a quasi-experiment, 3 used a systematic review, and 1 used a randomized controlled trial. The results of statistical tests for the 10 journals selected, all journals showed a significant influence on the nursing intervention carried out, namely Progressive Muscle Relaxation therapy in reducing anxiety in cancer sufferers. It is hoped that this literature review will become a reference and reference for nursing interventions in reducing anxiety in cancer patients, one of which is progressive muscle relaxation therapy.